2019
DOI: 10.1002/bit.27203
|View full text |Cite
|
Sign up to set email alerts
|

Development of a robust nitrilase by fragment swapping and semi‐rational design for efficient biosynthesis of pregabalin precursor

Abstract: Protein engineering is a powerful tool for improving the properties of enzymes. However, large changes in enzyme properties are still challenging for traditional evolution strategies because they usually require multiple amino acid substitutions. In this study, a feasible evolution approach by a combination of fragment swapping and semi‐rational design was developed for the engineering of nitrilase. A chimera BaNIT harboring 12 amino acid substitutions was obtained using nitrilase from Arabis alpine (AaNIT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…The enantiomeric excess (ee) of IBSN and CMHA were determined by chiral GC as described previously (Zhang et al, 2020).…”
Section: Enzyme Activity Assay and Kinetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The enantiomeric excess (ee) of IBSN and CMHA were determined by chiral GC as described previously (Zhang et al, 2020).…”
Section: Enzyme Activity Assay and Kinetic Analysismentioning
confidence: 99%
“…In our previous work, a robust nitrilase Ba NIT/L223Q/H263D/Q279E ( Ba NIT M0 ) was developed by fragment swapping and semi‐rational design, which catalyzed asymmetric hydrolysis of high concentration of IBSN (100 g/L) with excellent enantioselectivity (Zhang et al, 2020). However, it was found that Ba NIT M0 exhibited poor reaction specificity towards IBSN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all the characterized nitrilases, no common feature of protein sequences was found that could explain their stability, only highly specific motifs were proposed as being important, thus making protein engineering complicated. Nevertheless, some nice examples have been reported to overcome stability limitations of nitrilases ( Xu et al, 2018 ; Zhang et al, 2020 ) in addition to other engineering work targeting enantioselectivity/specificity or substrate inhibition at high loadings ( Stolz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes, as biocatalysts, have drawn considerable attention in many fields due to their advantages over conventional catalysts, such as their mild reaction conditions and high selectivity (Bornscheuer et al, 2012; Rudroff et al, 2018; Wu et al, 2020). However, many enzymes have drawbacks, such as low expression levels, poor activity, and low stability, which have severely limited their industrial applications (Zhang et al, 2020). Protein engineering effectively solves these inherent problems of enzymes (Bornscheuer, 2016; Chen & Arnold, 2020; Whitehead et al, 2020).…”
Section: Introductionmentioning
confidence: 99%